2003
DOI: 10.1074/jbc.m210497200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Interactions between DNA Polymerase and Single-stranded DNA-binding Protein in Bacteriophage RB69

Abstract: The organization and proper assembly of proteins to the primer-template junction during DNA replication is essential for accurate and processive DNA synthesis. DNA replication in RB69 (a T4-like bacteriophage) is similar to those of eukaryotes and archaea and has been a prototype for studies on DNA replication and assembly of the functional replisome. To examine protein-protein interactions at the DNA replication fork, we have established solution conditions for the formation of a discrete and homogeneous comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…No other chromatographic peaks at 280 or 260 nm were observed in the elution profile, suggesting that the low estimate is the result of an error in the calculation of dn/dc and the UV calibration constant for the protein⅐nucleic acid complex. A similar underestimate was observed for the mass of DNA polymerase⅐primer-template complexes (40). UP1 alone was somewhat polydispersed at the solution conditions used in these experiments (0.1 M KCl, 10 mM potassium cacodylate, pH 6.5).…”
Section: Up1 Interactions With 6-mi-substituted Telomeric Dnamentioning
confidence: 62%
See 1 more Smart Citation
“…No other chromatographic peaks at 280 or 260 nm were observed in the elution profile, suggesting that the low estimate is the result of an error in the calculation of dn/dc and the UV calibration constant for the protein⅐nucleic acid complex. A similar underestimate was observed for the mass of DNA polymerase⅐primer-template complexes (40). UP1 alone was somewhat polydispersed at the solution conditions used in these experiments (0.1 M KCl, 10 mM potassium cacodylate, pH 6.5).…”
Section: Up1 Interactions With 6-mi-substituted Telomeric Dnamentioning
confidence: 62%
“…The miniDAWN was calibrated according to the manufacturer's instructions (Wyatt Technology), and BSA was used as a standard to evaluate the accuracy of the system. A dn/dc value of 0.184 was used for BSA and single proteins (40). dn/dc values for complexes were determined by using both UV-visible detector (280 nm) and differential refractometer.…”
Section: Methodsmentioning
confidence: 99%
“…In the same system, DinI, a RecA regulator, has been shown to interact with activated RecA but not free RecA (80). In bacteriophage RB69, it is suggested that ssDNA binding by phage SSB induces a conformational change in SSB that allows it to associate specifically with adjacent SSB molecules and with its DNA polymerase, gp43 (70). These specific interactions are thought to be important for bacteriophage DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Functional and physical interactions have been described for all components of the replisome (2,9,19,20). The polymerase physically interacts with gp32, which has important consequences for the properties of gp43, such as higher affinity for the primer-template junction and increased processivity during DNA synthesis (21). The polymerase is in turn attached to the clamp protein through a well described interaction between the C terminus of the polymerase and the subunit interfaces of the trimeric clamp protein (5,6,22).…”
mentioning
confidence: 99%